2020
DOI: 10.1002/ejp.1652
|View full text |Cite
|
Sign up to set email alerts
|

Six‐year trends in postoperative prescribing and use of multimodal analgesics following total hip and knee arthroplasty: A single‐site observational study of pain management

Abstract: Background: Guidelines for acute postoperative pain management recommend administering analgesics in multimodal combination to facilitate synergistic benefit, reduce opioid requirements and decrease side-effects. However, limited observational research has examined the extent to which multimodal analgesics are prescribed and administered postoperatively following joint replacement. Methods: In this longitudinal study, we used three-point prevalence surveys to observe the 6-year trends in prescribing and use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…In a recent study by Khaw et al, in which physicians were presented guidelines for multimodal pain management prior to TJA procedures and follow-up visits, the proportion of unimodal prescribing in THA patients decreased from 53.7 to 6% over a 6-year period. 7 The results of this study demonstrate a similar transition from unimodal to multimodal consumption following MPMP implementation. Interestingly, the downward trend in opioid use seen in our study was not consistent over the study period, with a minor increase observed in 2020 (►Fig.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In a recent study by Khaw et al, in which physicians were presented guidelines for multimodal pain management prior to TJA procedures and follow-up visits, the proportion of unimodal prescribing in THA patients decreased from 53.7 to 6% over a 6-year period. 7 The results of this study demonstrate a similar transition from unimodal to multimodal consumption following MPMP implementation. Interestingly, the downward trend in opioid use seen in our study was not consistent over the study period, with a minor increase observed in 2020 (►Fig.…”
Section: Discussionsupporting
confidence: 63%
“…6 This acute pain predisposes patients to postsurgical complications such as decreased ambulation and mobilization, which may in turn lead to chronic pain and an overall reduced clinical outcome. [7][8][9] The extent of postoperative complications may be even more profound in patients undergoing rTHA, necessitating the study of additional methods of pain management. 10,11 Opioids are the most commonly utilized method of pain management in the postoperative recovery period following THA.…”
mentioning
confidence: 99%
See 1 more Smart Citation